2022
DOI: 10.1513/annalsats.202106-680oc
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Sequential Organ Failure Assessment Score across Patients with and without COVID-19 Infection

Abstract: Rationale Sequential organ failure assessment (SOFA) scores are commonly used in crisis standards of care policies to assist in resource allocation. The relative predictive value of SOFA by coronavirus disease (COVID-19) infection status and among racial and ethnic subgroups within patients infected with COVID-19 is unknown. Objectives To evaluate the accuracy and calibration of SOFA in predicting hospital mortality by COVID-19 infection status and across racial and eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…However, the association between mortality, ICU LOS and the APACHE II score for COVID-19 patients has been observed previously [ 16 , 17 ]. Early maximum SOFA (< 48 h from ICU admission) has been shown to be as discriminant in COVID-19 positive patients than COVID-19 negative patients [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the association between mortality, ICU LOS and the APACHE II score for COVID-19 patients has been observed previously [ 16 , 17 ]. Early maximum SOFA (< 48 h from ICU admission) has been shown to be as discriminant in COVID-19 positive patients than COVID-19 negative patients [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Roy et al found that Black patients had higher mean peak and mean 24-hour SOFA scores than patients of other races despite not having significantly greater ICU admission and in-hospital mortality rates. 5 Although Gershengorn and colleagues found SOFA accuracy to be consistent among racial and ethnic groups, 6 accuracy does not guarantee equitable treatment. In a large multisite cohort study, Miller et al found that Black patients' odds of dying were 2% lower than those of White patients with equivalent SOFA scores.…”
Section: Harms Of Using Sofamentioning
confidence: 99%
“…These typically require receipt of SARS-CoV-2 therapeutics (eg, dexamethasone or remdesivir) or need for supplemental oxygen in addition to a positive PCR. [3][4][5] Large cohort studies have also used different approaches for defining COVID-19 hospitalizations, including a positive PCR alone, [6][7][8][9] International Classification of Disease, Tenth Revision, Clinical Modification (ICD-10-CM) codes for COVID-19, [10][11][12][13][14][15][16][17][18] institutional definitions, or combinations of these. [19][20][21][22][23][24][25] Notwithstanding the panoply of definitions being used, few data are available that compare estimates of COVID-19 hospitalizations, severity of illness, mortality, and trends between definitions, nor their accuracy in identifying primary or contributing versus incidental infections.…”
mentioning
confidence: 99%